A Sensitive Triple Quadrupole Liquid Chromatography Mass Spectrometric Method for the Estimation of Valproic Acid in K2EDTA Human Plasma using Furosemide as the Internal Standard - Soni, K.; Patel, N.; Singh, K.; Jha, A.; Patel, H.; Gupta, R.; Srinivas, N. R. (Drug Research, 2016)
A valproic acid is primarily being used in the treatment of epilepsy is a histone deacetylase inhibitor and it is under investigation for treatment of HIV and various cancer indications. A specific, sensitive and fast bioanalytical LC-MS/MS method was developed with furosemide as an internal standard (IS) and thoroughly validated for the quantitation of valproic acid using turbo ion spray in negative ion mode. The analyte and IS was extracted using protein precipitation. The chromatographic separation of analytes from extracted matrix was achieved using a Chromolith RP 18e (2.0×50 mm) column with a gradient mobile phase comprising of acetonitrile and purified water with acetic acid. The elution of both peaks was achieved within 5.2 min, with retention times of 2.55 min and 1.67 min for valproic acid and IS, respectively. Quantitation of valproic acid was achieved by the pseudo SRM transition pairs (m/z 142.8→m/z 142.8), and SRM transition pair (m/z 328.8 →m/z 204.6) for internal standard.The calibration standards of valproic acid showed linear over a range from 50 to 40 000 ng/mL, with a lower limit of quantitation of 50 ng/mL with accuracy of 3.74% and precision of 5.06%. The bias for inter- and intra-batch assays was 1.24–6.14% and 3.85–11.84%, respectively; while the corresponding precision was 2.56–16.37% and 1.29–11.34%, respectively. The developed method was used to monitor valproic acid levels in clinical samples. Because of higher sensitivity, this method can be used for therapeutic drug monitoring in pediatric subjects.
Keywords: valproic acid (VPA); ultra high performance liquid chromatography; LC-MS/MS; method validation; plasma; pharmacokinetics; therapeutic drug monitoring